2012
DOI: 10.1038/psp.2012.2
|View full text |Cite
|
Sign up to set email alerts
|

A PBPK Model to Predict Disposition of CYP3A‐Metabolized Drugs in Pregnant Women: Verification and Discerning the Site of CYP3A Induction

Abstract: Besides logistical and ethical concerns, evaluation of safety and efficacy of medications in pregnant women is complicated by marked changes in pharmacokinetics (PK) of drugs. For example, CYP3A activity is induced during the third trimester (T3). We explored whether a previously published physiologically based pharmacokinetic (PBPK) model could quantitatively predict PK profiles of CYP3A-metabolized drugs during T3, and discern the site of CYP3A induction (i.e., liver, intestine, or both). The model accounted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 36 publications
4
101
0
Order By: Relevance
“…Probe substrate studies are, however, complicated by safety concerns about administering drugs to pregnant women in the absence of clear therapeutic benefit, and the fact that pregnancy is associated with a plethora of physiologic changes that can affect probe disposition in an unpredictable or uncharacterized manner. An approach that appears to be very useful in addressing these issues is physiologically based pharmacokinetic dmd.aspetjournals.org (PBPK) modeling Gaohua et al, 2012;Ke et al, 2012). PBPK modeling allows incorporation of physiologic changes together with changes in multiple enzymes into a model that is fitted to best describe the disposition of well characterized drugs.…”
Section: Knowledge On Enzyme-specific Changes During Pregnancymentioning
confidence: 99%
“…Probe substrate studies are, however, complicated by safety concerns about administering drugs to pregnant women in the absence of clear therapeutic benefit, and the fact that pregnancy is associated with a plethora of physiologic changes that can affect probe disposition in an unpredictable or uncharacterized manner. An approach that appears to be very useful in addressing these issues is physiologically based pharmacokinetic dmd.aspetjournals.org (PBPK) modeling Gaohua et al, 2012;Ke et al, 2012). PBPK modeling allows incorporation of physiologic changes together with changes in multiple enzymes into a model that is fitted to best describe the disposition of well characterized drugs.…”
Section: Knowledge On Enzyme-specific Changes During Pregnancymentioning
confidence: 99%
“…Among these is approximately a 2-fold induction of CYP3A activity during the third trimester (T3), as measured by 19-OH-midazolam formation clearance (Hebert et al, 2008). Based on genotyping data and modeling and simulation, we have shown that this induction of CYP3A activity is primarily due to induction of hepatic CYP3A4 activity (Hebert et al, 2008;Ke et al, 2012). Many drugs routinely prescribed to pregnant women are cleared by CYP3A enzymes, such as protease inhibitors (e.g., ritonavir), antihypertensive drugs (e.g., nifedipine), and hypoglycemics (e.g., glyburide).…”
Section: Introductionmentioning
confidence: 99%
“…A maternal PBPK model incorporating known physiologic parameters as well as maternal hepatic P450 activity in each trimester was recently developed Gaohua et al, 2012;Lu et al, 2012). We refined this PBPK model and showed that the PBPK model populated with CYP3A activity change, based on CL ORAL of midazolam, could accurately predict the T 3 disposition of other CYP3A-metabolized drugs, nifedipine and indinavir (Ke et al, 2012). A sensitivity analysis suggested that CYP3A induction in T 3 is most likely hepatic and not intestinal.…”
Section: Introductionmentioning
confidence: 99%